A Resource Reservation Protocol with Linear Traffic Prediction for OBS Networks. (15th July 2013) - Karamitsos, Ioannis; Bowerman, Chris
Abstract : This paper addresses the issue of providing resource reservation mechanism for OBS networks. We propose a linear prediction mechanism based on least mean square (LMS) method to reduce the burst delay at edge nodes. A reservation method is proposed to increase the reservation probability and to improve the delay reduction performance.